OPTIMIZATION OF MENAQUINONE-7 PRODUCTION UNDER SUBMERGED FERMENTATION BY BACILLUS THURINGIENSIS KLSG-9 - SANDHYA GAJARE,; LINGAPPA KATTIMANI,; SARFARAZ AHMED,; MAHESH DIVATAR,; SHIVALEE A, (International Journal of Pharma and Bio Sciences, 2016)
In the present study it was aimed to improve the concentration of Menaquinone -7 (MK-7) by the potent strain KLSG-9 isolated from soil sample of Gulbarga region, India. Phylogenetic analysis of KLSG-9 strain was done by 16S rRNA partial sequencing and it revealed that isolate belongs to the genus Bacillus. The highest similarity of 16S rRNA of KLSG-9 was shown with Bacillus thuringiensis Bt407. The obtained sequence was submitted to GenBank under the accession number KT326332. Physical as well as nutritional parameters were optimized to obtain maximum MK-7 yield. The optimum pH and temperature for MK-7 production was 7 and 40°C whereas inoculum size was 2 ml, agitation speed 160 rpm with incubation period of 120h. Soya peptone, sucrose and glycerol were the best nitrogen and carbon sources, respectively, among the phosphate sources tested K2HPO4 was found better source. In this regard with all optimum conditions we could achieve total 73 mg/L of MK-7 production.